The printable 3D model of Kyrenia Ship - Martins, Adolfo Miguel (My University, 2019)
This 3D model of a late Classical ship was inspired of what we know from the archaeological record. There are several versions of this reconstructed vessel, available in different formats. The outline of the present model was developed based on J. Richard Steffy’s drawings, with kind permission of Susan Katzev. However, it has been modified in order be 3D printed easily at home. For the detailed 3D model of the Kyrenia Ship please visit https://imareculture.eu/downloads/project-tools/3d-libraries-of-ships/.
Keywords: 3D model; 3D printing; Kyrenia; iMARECULTURE